Dampak Sosial Penerapan Kebijakan Sekolah Daring (Studi Pada SMA 10 Makassar) - Mardi Lestari A; Ahmadin Ahmadin; Najamuddin Najamuddin (Universitas Negeri Makassar, 2022)
This research aims to: 1) find out the implementation process of online school policy in SMA 10 Makassar. 2) find out the social impact arising from the implementation of online school. This research conducts using descriptive qualitative research methode. 16 informants. The data obtains by observation, interview and documentation. The data analysis use three stages: data reduction, data presentment and conclusion. The result of research are: 1) During the implementation of online school there are some technical problems such as, ownership of devices to participate in online learning, run out of internet quota, unstable internet network. 2) The positive impact of implementing online school are: Teaching and learning activities can still be carried out during the online covid-19 pandemic, Students have more time to interact with family at home, Students are more proficient in the use of technology in learning, Varied learning methods, because the space for learning does not have to be in the classroom or school. 3) The negative impact of implementing online school policies are: There is no emotional connection between teachers and students, character building does not work effectively in virtual media, Decrease in the achievement of students' scores on the course.